Novel antioxidant N-acetylcysteine amide prevents gp120-and Tat-induced oxidative stress in brain endothelial cells - (:unkn) unknown (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2006)
Free radical production and, consequently, oxidative stress play an important role in the pathogenesis of AIDS and cause damage to lipids, proteins, and DNA. In our previous study, the HIV-1 envelope glycoprotein (gp120) and transregulatory protein (Tat) of HIV-1 have been found to induce oxidative stress in an immortalized endothelial cell line from rat brain capillaries, RBE4 (in vitro model of the blood-brain barrier). Here, we have determined the effects of a novel antioxidant, N-acetylcysteine amide (NACA), on gp120- and Tat-induced oxidative stress. Various oxidative stress parameters, including reduced glutathione (GSH), oxidized glutathione (GSSG), catalase (CAT) activity, and glutathione reductase (GR) activity, as well as malondialdehyde (MDA) levels, were used as measures of oxidative stress. NACA significantly increased the levels of intracellular GSH, CAT, and GR and decreased the levels of MDA in RBE4 cells, showing that oxidatively challenged cells were protected. Gp120- and Tat-induced increases in intracellular reactive oxygen species (ROS) were observed by using the 2',7'-DCF assay; the ROS scavenger, NACA, blocked ROS generation. A well-known apoptosis indicator, caspase-3 activity, was measured and was also found to have been returned to its control levels by NACA. Treatment of RBE4 cells with gp120 and Tat caused an increase in toxicity, as measured by lactate dehydrogenase (LDH) and tetrazolium reduction (MTS) assays. HIV-1 protein-induced toxicity in these cells was blocked by treatment with NACA. These studies show that NACA reverses gp120- and Tat-induced oxidative stress in immortalized endothelial cells. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: antioxidants; blood-brain barrier; oxidative stress; gp120 protein; Tat protein; HIV-1; IN-VITRO MODEL; ACETYL CYSTEINE; NERVOUS-SYSTEM; RAT-BRAIN; BARRIER; HIV-1; GLUTATHIONE; MALONDIALDEHYDE; PERMEABILITY; APOPTOSIS